KONVERSI LAHAN PERTANIAN KE NON-PERTANIAN : FUNGSI EKOLOGIS YANG TERABAIKAN - Handoyo, Eko (Faculty of Social Science, Universitas Negeri Semarang, 2010)
Indonesia had always been known as an agricultural country, because most of the population ofÃ‚Â Indonesia worked as a farmer. The agricultural sector is suspected to contribute to the Gross DomesticÃ‚Â Product and has a strategic role in the Indonesian economy. Not only has that, done in a sustainableÃ‚Â agriculture also had an invaluable ecological function. But the sustainability of agriculture is threatenedÃ‚Â due to the function of the rapidly growing industrial activities that encourage the transfer function ofÃ‚Â agricultural land. Some things such as government policy to privatize the development of industrial areas,Ã‚Â policies that encourage large-scale residential development, investment and deregulation policies. TheÃ‚Â impact of policies over the functions of agricultural land, which is reduced which causes the vast fi eldsÃ‚Â of Ã‚Â rice Ã‚Â production Ã‚Â decreased Ã‚Â and Ã‚Â in Ã‚Â turn Ã‚Â threaten Ã‚Â the Ã‚Â self-suffi ciency Ã‚Â in Ã‚Â food, Ã‚Â rising unemployment,Ã‚Â investment Ã‚Â in Ã‚Â irrigation Ã‚Â abandoned, Ã‚Â increasing Ã‚Â non-productive Ã‚Â agricultural Ã‚Â land Ã‚Â and Ã‚Â the Ã‚Â decline Ã‚Â ofÃ‚Â wetland ecosystems and land. Governments seek to control the issuing of Act No. 41 of 2009, but seemÃ‚Â less successful to overcome the desire of investors to converted agricultural land into industrial zones andÃ‚Â housing. These laws have a mission to restore the ecological functions of agricultural land, diversifi cationÃ‚Â of biodiversity, fl ood control, erosion and pollution prevention.Key words: conversion, agriculture, ecological